Frequency of Maternal and Fetal Outcome in Pregnant Women Complicated By Preterm Premature Rupture of the Membranes before 34 Weeks of Gestation at Tertiary Care Hospital, Karachi - Khan, Mehar Fryal; Depar, Asma Ali; Majeed, Aiman (Indus Journal of Bioscience Research, 2025)
Introduction: Significant perinatal morbidity and death may result from preterm premature rupture of membranes (PPROM) occurring before 34 weeks, which presents major hazards to the health of both the mother and the fetus. To maximize results, managing PPROM requires a precise diagnosis and educated choices. Methodology: Over the course of six months, from May 20 to November 20, 2021, this descriptive, prospective research was carried out at Aga Khan University Hospital in Karachi. Non-probability sequential sampling was used to enroll 110 individuals with PPROM before to 34 weeks. Singleton pregnancies and gestational age ≤34 weeks, as verified by the latest menstrual cycle and ultrasound, were among the inclusion criteria. Patient demographics, medical history, and markers like fetal activity and amniotic fluid properties were all part of the data gathering process. SPSS Version 20 was used to evaluate the results, and a chi-square test was used to check for significance (p-value < 0.05) after stratification. Results: The research found that newborn outcomes, with respiratory distress syndrome (RDS) being the most prevalent, and mother outcomes, such as chorioamnionitis and postpartum hemorrhage, were significant. 68.2% of patients needed NICU admission. Lower gestational age at rupture was linked to a higher risk of complications, underscoring the need of attentive prenatal care. Conclusion: Families and healthcare systems bear a heavy price as a result of PPROM’s substantial contribution to poor mother and newborn outcomes. To successfully manage PPROM, a precise diagnosis and risk-benefit analysis are essential. Neonatal outcomes may be improved and healthcare expenses can be decreased with conservative treatment depending on gestational age.